Applied mathematics, its importance in developing it in Peru - Ortiz Fernández, Alejandro (2025)
The objective of this article is to contribute with some ideas and proposals with the purpose of further developing the study and research in our country of this area of mathematics, given the historical background of how, thanks to it, many countries have achieved their technological development and in this way with the well-being of the respective society.